2017
DOI: 10.1152/japplphysiol.00909.2016
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dietary nitrate supplementation on physiological and muscle metabolic adaptations to sprint interval training

Abstract: We hypothesized that 4 wk of dietary nitrate supplementation would enhance exercise performance and muscle metabolic adaptations to sprint interval training (SIT). Thirty-six recreationally active subjects, matched on key variables at baseline, completed a series of exercise tests before and following a 4-wk period in which they were allocated to one of the following groups: ) SIT and [Formula: see text]-depleted beetroot juice as a placebo (SIT+PL);) SIT and [Formula: see text]-rich beetroot juice (~13 mmol [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
41
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 78 publications
(127 reference statements)
4
41
2
Order By: Relevance
“…Ferguson et al (2013) found that the fall in oxygen cost/ delivery ratio at contraction onset was slowed after BRJ administration in rats, reflecting an improved metabolic control (Ferguson et al 2013a). Decreased metabolic perturbation measured in lactate concentration was found in other studies as well, in both rats (Ferguson et al 2013b) and humans (Carriker, Mermier, et al 2016; C. Thompson et al 2017). One study specifically tested nitrate supplementations in subjects exposed to a state of hypoxia, and found that BRJ increased tolerance to exercise and oxidative function values to values normally found in normoxia, and decreased metabolic perturbation in hypoxia ).…”
Section: General Effects Of Brj On Skeletal Muscles and Oxygen Consumsupporting
confidence: 61%
See 3 more Smart Citations
“…Ferguson et al (2013) found that the fall in oxygen cost/ delivery ratio at contraction onset was slowed after BRJ administration in rats, reflecting an improved metabolic control (Ferguson et al 2013a). Decreased metabolic perturbation measured in lactate concentration was found in other studies as well, in both rats (Ferguson et al 2013b) and humans (Carriker, Mermier, et al 2016; C. Thompson et al 2017). One study specifically tested nitrate supplementations in subjects exposed to a state of hypoxia, and found that BRJ increased tolerance to exercise and oxidative function values to values normally found in normoxia, and decreased metabolic perturbation in hypoxia ).…”
Section: General Effects Of Brj On Skeletal Muscles and Oxygen Consumsupporting
confidence: 61%
“…In several studies, ingestion of BRJ was found to significantly decrease VO 2 , regardless of the duration of BRJ consumption and type of intervention Kelly et al 2014;Kuennen et al 2015;Lansley, Winyard, Fulford, et al 2011;Masschelein et al 2012;Muggeridge et al 2013Muggeridge et al , 2014Rienks et al 2015;Tan et al 2018;Thompson et al 2017;Vanhatalo et al 2010;Whitfield et al 2016;Wylie, Kelly, Fulford, et al 2013). Tan et al (2018) found that a 3day supplementation of BRJ before, and ingestion of BRJ during moderate-intensity exercise attenuated the increase in VO 2 that normally accompanies sportive performance, compared to placebo (Tan et al 2018).…”
Section: General Effects Of Brj On Skeletal Muscles and Oxygen Consummentioning
confidence: 98%
See 2 more Smart Citations
“…One possible approach involves the study of dietary factors that may act as ergogenic aids via their actions on cardiovascular function. For example, acute supplementation with beet root juice, which is high in nitrates, has been shown to enhance cardiac output and oxygen utilization and reduce vascular resistance and blood pressure at a given sub-maximal work intensity [2,3]. These effects are indicative of increased O 2 delivery to skeletal muscle.…”
mentioning
confidence: 99%